2001
DOI: 10.1164/ajrccm.163.3.2007120
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Insulin-Dependent Diabetes on Ventilatory Control in the Mouse

Abstract: Insulin-dependent diabetes mellitus (IDDM) can lead to ventilatory depression and decreased sensitivity to hypercapnia. We examined relationships between ventilation, plasma insulin, leptin, ketones, and blood glucose levels in two mouse models of IDDM: (1) streptozotocin-induced diabetes in C57BL/6J mice on a regular diet or with induced obesity from a high fat diet; and (2) spontaneous diabetes mellitus in NOD-Ltj mice. In both mouse models, IDDM resulted in depression of the hypercapnic ventilatory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 29 publications
0
35
0
1
Order By: Relevance
“…Moreover, serum leptin was reduced in untreated DKA mice as observed in children with type-1 diabetes presenting with DKA (17). In contrast, leptin increases in untreated DKA in both human adults and in an adult mouse model of diabetes (24,34).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, serum leptin was reduced in untreated DKA mice as observed in children with type-1 diabetes presenting with DKA (17). In contrast, leptin increases in untreated DKA in both human adults and in an adult mouse model of diabetes (24,34).…”
Section: Discussionmentioning
confidence: 88%
“…DKA was also observed in adult rats 48 h after injection with ALX (21), and in adult rabbits and dogs injected with STZ/ALX (22,23). The only mouse study to demonstrate ketosis involved STZ-treated adult mice fed a high-fat diet for 16 wk (24). We characterized a juvenile mouse model of DKA, as DKA-CE is almost exclusively a pediatric pathology (2,25).…”
Section: Discussionmentioning
confidence: 99%
“…Weakness might result from nonenzymatic glycosylation (glycation) of muscle fibres ( fig. 4) [170,171]. Rarely, diaphragmatic weakness results from diabetic neuropathy of the phrenic nerves [172,173], which can occur despite the absence of peripheral neuropathy [173].…”
Section: Respiratory Musclesmentioning
confidence: 99%
“…Insulin-dependent diabetes mellitus can lead to an overall depression of ventilatory control mechanisms (19). Indeed, several studies have shown a strong association of obstructive sleep apnea syndrome (OSAS) with obesity, male gender (androidcentral obesity), post-menopausal women, hypertension and diabetes, factors associated with metabolic syndrome (20)(21)(22)(23)(24)(25).…”
Section: Implications Of Metabolic Impairments In Sleepmentioning
confidence: 99%